Flame-Retardant and Smoke Suppression Properties of Nano MgAl-LDH Coating on Bamboo Prepared by an In Situ Reaction. (22nd May 2019) - Yao, Xiaoling; Du, Chungui; Hua, Yating; Zhang, Jingjing; Peng, Rui; Huang, Qiuli; Liu, Hongzhi
Abstract : In recent years, bamboo has been widely used for building materials and household goods. However, bamboo is flammable, so a flame-retardant treatment for bamboo is urgently needed. In this work, nano MgAl-layered double hydroxide (MgAl-LDH) coated on bamboo, which was called MgAl-LB, was synthesized by an in situ one-step method. To determine the optimal in situ time, the effects of different reaction times on LDH growth on the bamboo surface and the flame retardancy of the MgAl-LBs were investigated. The SEM observations show that LDH growth on the surface of bamboo was basically saturated when the in situ reaction time was 24 h. Abrasion experiments show that MgAl-LDH coating has good abrasion resistance. The fire performance of the MgAl-LBs was evaluated by cone calorimeter tests, which indicated that the THR and TSP of the MgAl-LBs were significantly lower than those of untreated bamboo. Taking into account the energy consumption problem, determining the reaction time of 24 h is the optimal reaction time. Compared with untreated bamboo, the THR and TSP of MgAl-LB prepared at 24 h decreased by 33.3% and 88.9%, respectively.